Design Of Financial Information System in Web-Based Trading Unit: Case Study of Lerta Rahayu Village Owned Business Entity, Samida Village - Septiani, Windi Centia; Sudrajat, Adjat; F, Ganjar Nurul; Dianto, Aris (Electronic, Business, Management and Technology Journal, 2024)
The swift advancement of technology has heightened awareness regarding the significance of employing technology throughout many facets of life, particularly information technology. An example of this is financial information systems, which facilitate efficient data administration within firms. The Village-Owned Enterprise Kerta Rahayu in Samida Village, a nascent institution, encounters difficulties in overseeing its business divisions and financial management, which are still traditionally organized and susceptible to inaccuracies, especially within the trading unit. This study intends to construct a web-based Financial Information System utilizing the Extreme Programming methodology, PHP, MySQL, and the CodeIgniter3 framework. This system aims to enhance efficiency and mitigate the risk of errors in handling financial and inventory data, hence facilitating improved company management. The ramifications of this discovery are substantial. Implementing this Financial Information System will improve transparency and accountability in financial operations, facilitating expedited decision-making via real-time data availability. The system could also be a prototype for other village-owned firms encountering analogous issues, fostering more technology integration in local governance and business administration. This research ultimately aids in formulating sustainable practices that can improve the community's economic welfare. The financial information system comprises four primary participants: the master administrator, the village chief, the general director or chairman of BUMDes, and the BUMDes treasurer. The master administrator oversees the system to guarantee efficient functioning, while the other participants operate as report evaluators.